Analisis Kesalahan Sintaksis Peserta Lomba Debat Bahasa Arab - Majid, Muhamad Nurkolis; Fathian, Fitraman; Wahyudin, Dedih (IAIN Bone, 2025)
Debate method is currently widely used in language learning, this method is very appropriate and effective in improving foreign language skills. Through the debate method, students are required to think logically and provide direct responses, so that these demands can improve students' language skills.Â The Arabic debate method that is widely used in Indonesia refers to the Qatari debate system. The purpose of this research is to reveal and describe syntactic errors in Arabic debate competition videos so that they can provide solutions to syntactic errors made by speakers. This research is a descriptive qualitative research, the sample in this research is the final video of the SAFAR 13 Arabic debate competition organized by the State University of Jakarta. The results of this study reveal syntactic errors consisting of 9 errors in the use of isim majrur, 24 errors in tadzkir and ta'nis, 6 errors in nasab isim, 1 error in dhomir, 3 errors in maf'ulun bihi, 2 errors in idofat, and 2 errors in mubtada. It is expected that debaters routinely practice structured speaking with a focus on the use of correct sentences, improve their understanding of Arabic language structures, and conduct debate simulations with direct evaluation from coaches who can directly assess and evaluate syntactic errors made by debaters so as to minimize syntactic errors in Arabic debate competitions.